2018
DOI: 10.31234/osf.io/3bux8
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The relationship between vigilance capacity and physical exercise: A mixed-effects multistudy analysis

Abstract: A substantial body of work has depicted a positive association between physical exercise and cognition, although the key factors driving that link are still a matter of scientific debate. Here, we aimed to contribute further to that topic by pooling the data from seven studies (N=361) conducted by our research group to examine whether cardiovascular fitness (VO2), sport type participation (externally-paced [e.g., football or basketball] and self-paced [e.g., triathlon or track and field athletes] vs. sedentary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Another possible explanation is that golf putting is a self-paced task that is different from externally paced sports, such as football or basketball. As previous studies using psychomotor vigilance tests found that externally paced sports required shorter reaction times than self-paced sports (Ballester et al, 2018; Sanabria et al, 2019), our participants’ self-paced performance may have been more resistant to decreased vigilance owing to sleepiness. As our study showed the effect of just one night of SR, we might expect still greater relationships between chronic sleep loss, especially related to jet lag manifested in elite golfers, and performance; and future empirical research should address this possibility.…”
Section: Discussionmentioning
confidence: 57%
“…Another possible explanation is that golf putting is a self-paced task that is different from externally paced sports, such as football or basketball. As previous studies using psychomotor vigilance tests found that externally paced sports required shorter reaction times than self-paced sports (Ballester et al, 2018; Sanabria et al, 2019), our participants’ self-paced performance may have been more resistant to decreased vigilance owing to sleepiness. As our study showed the effect of just one night of SR, we might expect still greater relationships between chronic sleep loss, especially related to jet lag manifested in elite golfers, and performance; and future empirical research should address this possibility.…”
Section: Discussionmentioning
confidence: 57%
“…Among the physiological variables, oxygen consumption is interpreted in the literature as the main index of aerobic fitness during exercise. 26 In view of this, in Pediatrics, the study by Bos et al 27 used VO 2 peak to determine the level of physical activity and the aerobic fitness of children aged 6 to 12 undergoing liver transplantation. The assessment consisted of the gas analysis measured using the cardiopulmonary exercise test (CPET), considered the gold standard for this assessment.…”
Section: Discussionmentioning
confidence: 99%
“…Further, it has also been proposed that nonathletes with a high CRF may have a better ability to allocate attentional resources over time compared to nonathletes with a low CRF during a sustained attention task ( Ciria et al, 2017 ). Further, Sanabria et al (2019) speculated that the relationship between CRF and sustained attention may be dependent on the type of sport being conducted. Given that rock climbing has been shown to independently have both a high CRF ( Fryer et al, 2017 ) and a high attention demand ( Bourdin et al, 1998 ; Green and Helton, 2011 ), CRF may be a physiological mediator that could at least in part explain on-sight and red-point ability.…”
Section: Introductionmentioning
confidence: 99%